CREATIVE RESPONSES TO COVID-19 PANDEMIC IN LITHUANIA: FROM NEOLOGISMS TO REINTERPRETATION OF FOLKLORE - Agnė Aleksaitė; Rita Urnėžiūtė (Вісник Київського національного університету імені Тараса Шевченка. Літературознавство. Мовознавство. Фольклористика, 2024)
Background. The coronavirus pandemic that reached Lithuania in the early spring of 2020 left its mark on language as well. The emergence of neologisms and new phrases was observed during the first weeks of the quarantine, which was imposed in mid-March 2020.